Changing US Attributes After CS-US Pairings Changes CS-Attribute-Assessments: Evidence for CS-US Associations in Attribute Conditioning. (March 2016) - Förderer, Sabine; Unkelbach, Christian
Attribute Conditioning (AC) refers to people's changed assessments of stimuli's (CSs) attributes due to repeated pairing with stimuli (USs) possessing these attributes; for example, when an athletic person (US) is paired with a neutral person (CS), the neutral person is judged to be more athletic after the pairing. We hypothesize that this AC effect is due to CSs' associations with USs rather than direct associations with attributes. Three experiments test this hypothesis by changing US attributes after CS-US pairings. Experiments 1 and 2 conditioned athleticism by pairing neutral men (CSs) with athletic and non-athletic USs. Post-conditioning, USs' athleticism was reversed, which systematically influenced participants' assessment of CS athleticism. Experiment 3 conditioned athleticism and changed USs' musicality after CS-US pairings. This post-conditioning change affected musicality assessments of CSs but did not influence athleticism-assessments. The results indicate that AC effects are based on an associative CS-US-attribute structure.